Sistem Informasi Distribusian Dana Zakat Nasional pada Baznas Mukomuko Bengkulu Berbasis Web - Vivi Anggraini; Firna Yenila (Jurnal Informasi dan Teknologi, 2020)
National Amil Zakat Agency (BAZNAS) is an institution that processes the recipient and distribution of funds. Funds that are managed are sourced from individual zakat or an organization, so that at any time have data that requires speed in its processing. So this research was conducted to improve efficiency and effectiveness in the management and distribution of zakat funds in an information system. Data management uses Hypertext Preprocessor (PHP) programming software and its storage uses Structured Query Language (MySQL). The processed data are the recipient data and distribution of zakat in Bengkulu Mukomuko BAZNAS. The results of this study can manage data reception and distribution quickly and accurately as well as storing archived data safely. So that the use of information technology in processing zakat data can be managed better.